2013
DOI: 10.1007/s00213-013-3361-9
|View full text |Cite
|
Sign up to set email alerts
|

An organoselenium compound improves behavioral, endocrinal and neurochemical changes induced by corticosterone in mice

Abstract: These findings suggest a modulation of both serotonergic and glutamatergic systems by F-DPS after a long-term corticosterone exposure in mice, which may be involved in the antidepressant- and anxiolytic-like actions of this organoselenium compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…The latency to chew the pellet was recorded by an observer blind to this test. Immediately afterwards animals were returned in their home cage (Gai et al, 2014;Tang et al, 2015).…”
Section: Novelty Suppressed Feeding Testmentioning
confidence: 99%
“…The latency to chew the pellet was recorded by an observer blind to this test. Immediately afterwards animals were returned in their home cage (Gai et al, 2014;Tang et al, 2015).…”
Section: Novelty Suppressed Feeding Testmentioning
confidence: 99%
“…Considering that the MSG model induced a deregulation in the HPA axis (Dolnikoff et al 2001), which results in an increase in plasma corticosterone levels associated to a deregulation in the metabolic homeostasis and that another organoselenium compound normalizes the levels of corticosterone in mice (Gai et al 2014), the possibility that (p-ClPhSe) 2 restored hypercorticosteronemia induced by MSG administration could not be ruled out. As the limitations of the present study, the effects of (p-ClPhSe) 2 on the HPA axis and AMPK have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated the involvement of serotonergic system in the antidepressant-like action of F-DPS (Gai et al, 2013;Gay et al, 2010). Acute antiimmobility effect of this selenophene compound was significantly blocked by serotoninergic receptor antagonists and both acute and subchronic treatments with F-DPS inhibited serotonin uptake in a synaptosomal preparation from prefrontal cortex and hippocampus of mice (Gai et al, 2013;Gay et al, 2010). Thus, we considered F-DPS as the most promising selenophene to further investigate the mechanisms involved on its antidepressant-like action.…”
Section: Ctrlmentioning
confidence: 99%
“…Over the last decade preclinical studies have demonstrated that several organoselenium compounds have pharmacological properties including antioxidant, anticonvulsant, neuroprotective and antidepressant actions (Bruning et al, 2011;Dias et al, 2014;Gai et al, 2013;Mahadevan et al, 2013;Pinton et al, 2013;Wilhelm et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation